Too much pressure? Retailer power and occupational health and safety in the food processing industry - Lloyd, C; James, S (2008)
This article examines the impact of supply chain pressures on the UK food processing industry and the implications for occupational health and safety. Based upon case studies in three meat processing plants, the research found that although the number of accidents is declining, little progress has been made in dealing with the widespread ill-health problems associated with largely repetitive and, in some cases, heavy work regimes. Supermarkets play a contradictory role in that they provide incentives to improve health and safety while at the same time their price and delivery demands have a detrimental impact. Despite these intense supply chain pressures, there is some room for 'manoeuvrability' in that both employers and workplace trade unions can make a difference to health and safety outcomes. © 2008 BSA Publications Ltd®.